Health Financing Reform in Thailand : Toward Universal Coverage under Fiscal Constraints - Hanvoravongchai, Piya (World Bank,Washington DC, 2013)
Thailand's model of health financing and its ability to rapidly expand health insurance coverage to its entire population presents an interesting case study. Even though it is still a middle-income country with limited fiscal resources, the country managed to reach universal health insurance coverage through three main public schemes: the Universal Coverage Scheme (UCS), the Social Security Scheme (SSS), and the Civil Servant Medical Benefit Scheme (CSMBS). The UCS, which is the largest and most instrumental scheme in the expansion of coverage to the poor and to those in the informal sector, is the focus of this report. It describes the nuts and bolts of the UCS as a key component of the health financing system in Thailand. It analyzes Thailand's experience in health insurance coverage expansion within limited fiscal constraints through various mechanisms to contain costs. It also explores the two commonly discussed approaches for the universal coverage movement: the expansion model (starting from covering the poor and formal sector to universal coverage) and the comprehensive approach (covering the entire population at the same time).